The results of three times repeated filling cystometry and pressure flow studies in children with non‐neurogenic lower urinary tract dysfunction. Issue 5 (14th April 2022) - Ergun, Raziye; Sekerci, Cagri Akin; Tanidir, Yiloren; Ozturk, Naime İpek; Tarcan, Tufan; Yucel, Selcuk
Abstract: Aim: We previously reported that some urodynamic parameters change with repetitive filling in children with neurogenic lower urinary tract dysfunction (LUTD). In this study, we aimed to search if three‐times repeated filling cystometries (FC) and pressure‐flow studies (PFS) would change the urodynamics parameters in children with non‐neurogenic LUTD. Materials and Methods: All children with three repeated FC and PFS between June 2017 and December 2018 were included in the study. Urodynamic reports and charts were evaluated retrospectively. The first sensation of bladder filling (FSBF), maximum cystometric capacity (MCC), detrusor pressure at the FSBF (Pdet.first.sens ), maximum detrusor pressure during filling (Pdet.fill.max ), presence of detrusor over activity, compliance, maximum urine flow (Qmax), detrusor pressure at the maximum urine flow (PdetQmax), residual urine and presence of detrusor sphincter dyssynergy (DSD) were compared among three‐times repeated urodynamic studies. Results: Forty children were included in the study. 27 (67.5%) were girls and 13 (32.5%) were boys. Median age was 9 (3.4–17) years. Indications were LUTD with low grade vesicoureteral reflux in 19 (47.5%), LUTD refractory to conservative management in 13 (32.5%), urinary tract infection with LUTD in 6 (15%) and secondary enuresis in 2 (5%). Pdet.first.sens, presence of DO, MCC, Qmax, PdetQmax, residual urine, flow pattern, and presence of DSD were comparable in all three repeated tests. The third FC may show decreased filling detrusor pressures and increased compliance with no change on capacity. Conclusion: In children with non‐neurogenic LUTD, three‐times repeated FC and PFS present comparable results except FSBF, Pdet.fill.max, and compliance at the third test.